(untitled) (International Seminar on Syariah and Law (INSLA), 2020)
This paper analyses the international experiences of various jurisdictions that may be taken as lessons for Malaysia. The discussion touches on the feasibility of making international comparisons in child care settings, in order to enhance the quality of child care settings in terms of laws and regulations. Experiences from other countries are scrutinised here in order to take lessons from these countries. Looking into child care in the prisms of international perspectives will assist Malaysia in improving and developing the Malaysian child care, specifically on laws and regulations. The paper aims to present experiences from other countries, which can be a valuable reference for Malaysia to work on improving the Malaysian child care legislative framework.